REKRUTMEN POLITIK DAN KOMUNIKASI POLITIK PARTAI GERINDRA DALAM KANDIDASI WALIKOTA BANDUNG 2024-2029 - Sabarudin, Didin (KOMUNIKA BANGSA, 2024)
Abstract Indonesia is facing simultaneous national regional head elections in 2024 to elect Governors, Regents, and Mayors in 38 provinces and 514 districts and cities. Political parties have a central position in regional head elections through political recruitment to take part in electoral competitions at all levels in accordance with the mandate given by laws and regulations regarding political parties, general elections, and regional head elections. The recruitment of the Gerindra party for the candidate for Mayor/Deputy Mayor of Bandung is recommended to Prabowo Subianto's trusted young figure, R. Dhani Wirianata number 07-1051/REKOM/DPP-GERINDRA/2024 dated 18 July 2024 which was signed by the General Chairperson and Secretary General after going through selection with open and closed methods. Dhani's figure is believed to be able to accelerate development and solve the problems of the city of Bandung as the political communication of the Gerindra party in the form of political messages and public opinion is conveyed through the candidacy declaration of R. Dhani Wirianata carrying the tagline "Bandung Together with Advanced Indonesia". The study approach was carried out using a qualitative method with exploratory characteristics to capture the meaning and understand the political recruitment and political communication of the Gerindra party behind the reality of R. Dhani Wirianata's candidacy. This means that the process of political recruitment and political communication in the 2019 Solo city elections is likely to happen again in the 2024 Bandung city elections. Abstrak Indonesia menghadapi perhelatan pemilihan kepala daerah serentak secara nasional tahun 2024 untuk memilih Gubernur, Bupati, dan Walikota di 38 provinsi serta 514 kabupaten dan kota. Kedudukan partai politik memiliki posisi sentral dalam pemilihan kepala daerah melalui rekrutmen politik untuk mengikuti kompetisi pemilihan pada semua jenjang tingkatan sesuai dengan mandat yang diberikan oleh peraturan perundangan tentang partai politik, pemilihan umum, dan pemilihan kepala daerah. Rekrutmen partai Gerindra untuk kandidasi Walikota/Wakil Walikota Bandung direkomendasikan kepada sosok muda kepercayaan Prabowo Subianto, R. Dhani Wirianata bernomor 07-1051/REKOM/DPP-GERINDRA/2024 tanggal 18 Juli 2024 yang ditandatangani oleh Ketua Umum dan Sekretaris Jenderal setelah melalui seleksi dengan metode terbuka dan tertutup. Sosok Dhani diyakini mampu mengakselerasi pembangunan dan mengurai permasalahan kota Bandung sebagai komunikasi politik partai Gerindra dalam bentuk pesan politik dan opini publik disampaikan melalui deklarasi pencalonan R. Dhani Wirianata dengan mengusung tagline “Bandung Bersama Indonesia Maju”. Pendekatan kajian dilakukan dengan metode kualitatif berciri eksploratori untuk menangkap makna dan memahami rekrutmen politik dan komunikasi politik partai Gerindra di balik realitas kandidasi R. Dhani Wirianata. Maknanya, proses rekrutmen politik dan komunikasi politik pada pilkada kota Solo 2019 memungkinkan berulang terjadi pula pada pilkada kota Bandung 2024.